The Effectiveness of the Risk Committee, Political Relations and Company Performance in the Banking Industry in Indonesia - Darmawan, Rexy; Rombebunga, Meyjerd; Leon, Farah Margaretha (Universitas Pendidikan Ganesha, 2021)
This study aims to analyze the relationship between the effectiveness of the risk committee, political relations and company performance in the banking industry in Indonesia which is listed on the Indonesia Stock Exchange (BEI). The data were obtained using purposive sampling, so that 41 companies were obtained for 2017 to 2019 using the Stata analysis tool. The results of this study indicate a significant positive effect between the total risk committee members on company performance as proxied by ROA. In addition, the existence of a political relationship as a moderator indicates a negative influence between the number of meetings and concurrent positions in the risk committee on company performance with the proxy of ROA. In order to improve company performance, the risk committee must increase the number of members in the risk committee so that they can exchange ideas to solve company problems. Furthermore, political relations have a negative impact on company performance. Spending more money to win business projects and government licensing can increase costs which can directly reduce company performance.